Genetic variants in the promoter region of the calcium‐sensing receptor gene are associated with its down‐regulation in neuroblastic tumors. Issue 4 (24th November 2016) - Masvidal, Laia; Iniesta, Raquel; García, Marta; Casalà, Carla; Lavarino, Cinzia; Mora, Jaume; de Torres, Carmen
Abstract : We have previously reported that the calcium‐sensing receptor (CaSR) is expressed in benign, differentiated neuroblastic tumors, and epigenetically silenced in undifferentiated, malignant cases. Furthermore, cinacalcet, an allosteric activator of the CaSR, reduces neuroblastoma tumor growth in preclinical models. However, to identify patients that might benefit from this treatment, a complete understanding of mechanisms governing CaSR expression in these tumors would be required. We have now analyzed two polymorphisms in the promoter region of the CASR gene (rs7652589 and rs1501899) by allelic discrimination in neuroblastoma patients and cell lines. Association of genotypes and haplotypes with CaSR mRNA levels and CASR promoter P2 methylation status was determined. Data presented show that minor alleles rs7652589 and rs1501899, present either in homo‐ or heterozygosis, were correlated with reduced CaSR mRNA levels in matching primary tumors and this association was independent of CASR promoter P2 hypermethylation. Haplotype AA was independently associated with reduced CaSR expression after adjusting by promoter P2 methylation status. These polymorphisms were identified in some ganglioneuromas in which CaSR expression is low despite exhibiting a high degree of differentiation. Furthermore, homozygous variants rs7652589 and rs1501899 were detected in SH‐SY5Y cells, which are devoid of CaSR expression in the absence of hypermethylation of CASR promoter P2. In summary, minor alleles rs7652589 and rs1501899 are associated with reduced CaSR expression in neuroblastic tumors and neuroblastoma cell lines in which the CASR gene promoter P2 is not hypermethylated. Therefore, they potentially represent an additional mechanism of CASR transcriptional regulation in this group of developmental malignancies. © 2016 Wiley Periodicals, Inc.